Medical Interpreting in Canada's North - Peter, Jacopoosie (Meta, 1993)
AbstractThis article provides some insight into the historical development of the health care system in Canada's Eastern Arctic from the Second World War to the present. It discusses some of the issues related to the quality of medical interpretation services in the NWT, such as the age of the interpreter and competence in both languages. A short discussion on the use of generalized versus specialized terminology is also included.